Efficacy of a single intramuscular injection of porcine FSH in hyaluronan prior to ovum pick-up in Holstein cattle - Vieira, L. M.; Rodrigues, C. A.; Castro Netto, A.; Guerreiro, B. M.; Silveira, C. R.A. [UNESP]; Freitas, B. G.; Bragança, L. G.M.; Marques, K. N.G.; Sá Filho, M. F.; Bó, G. A.; Mapletoft, R. J.; Baruselli, P. S. (Elsevier, 2016)
Plasma FSH profiles, in vitro embryo production (IVP) after ovum pickup (OPU), and establishment of pregnancy with IVP embryos were compared in untreated Holstein oocyte donors and those superstimulated with multiple injections or a single intramuscular (IM) injection of porcine FSH (pFSH) in hyaluronan (HA). Plasma FSH profiles were determined in 23 heifers randomly allocated to one of four groups. Controls received no treatment, whereas the F200 group received 200 mg of pFSH in four doses, 12 hours apart. The F200HA and F300HA groups received 200- or 300-mg pFSH in 5 mL or 7.5 mL, respectively of a 0.5% HA solution by a single IM injection. Plasma FSH levels were determined before the first pFSH treatment and every 6 hours over 96 hours. All data were analyzed by orthogonal contrasts. Circulating FSH area under curve (AUC) in pFSH-treated animals was greater than that in the control group (P = 0.02). Although the AUC did not differ among FSH-treated groups (P = 0.56), the total period with elevated plasma FSH was greater in the F200 group than in the HA groups (P < 0.0001). However, the F300HA group had a greater AUC than the F200HA group (P = 0.006), with a similar total period with elevated plasma FSH (P = 0.17). The IVP was performed in 90 nonlactating Holstein cows randomly allocated to one of the four treatment groups as in the first experiment. A greater proportion of medium-sized (6-10 mm) follicles was observed in cows receiving pFSH, regardless of the treatment group (P < 0.0001). Also, numbers of follicles (P = 0.01), cumulus-oocyte complexes (COCs) retrieved (P = 0.01) and matured (P = 0.02), cleavage rates (P = 0.002), and blastocysts produced per OPU session (P = 0.06) were greater in cows receiving pFSH, regardless of the treatment group. Cows in the F200HA group had a greater recovery rate (P = 0.009), number of COCs cultured (P = 0.04), and blastocysts produced per OPU session (P = 0.06) than cows in the F300HA group. Similar pregnancy rates were observed 50 to 60 days after transferring IVP embryos from donors in the different treatment groups (P > 0.05). In conclusion, a single IM injection of pFSH combined in 0.5% HA resulted in similar plasma FSH profiles as twice-daily pFSH treatments. Treatment of nonlactating donors with pFSH, with or without HA, resulted in increased IVP over untreated controls. A single dose of 200 mg of pFSH in 0.5% HA resulted in greater IVP than 300-mg pFSH in HA. Finally, pregnancy rates with IVP embryos were similar, regardless donor treatment.
Keywords: Bos taurus; Bovine; Follicle-stimulating hormone half-life; In vitro embryo production; Oocyte competence